Fabrication and Characterization of Aluminum-Doped ZnO Nanorods for Biosensor Applications - Chou, Hsin-Yu; Chen, Yu-Wei; Yu, Chang-Tze Ricky; Chen, Jo-Mei Maureen; Chiang, Wei-Hsiang; Singh, Anoop Kumar; Kung, Po-Kai; Chiang, Jung-Lung; Wuu, Dong-Sing (IEEE sensors journal, 2025)
In this study, we prepared various aluminum-doped zinc oxide (AZO) surface structures via chemical bath deposition (CBD) for use in biomedical sensors. Indium tin oxide (ITO) conductive films were deposited on glass substrates via electron beam evaporation, and AZO nanorods were subsequently grown on the ITO layer using CBD at a bath temperature of 90~^{° } C. The AZO/ITO sensor electrode was further optimized through furnace annealing, improving its structural and electrical properties. This nanostructure enhances the ability of biomedical sensor films to adsorb H+ and OH {}^{-} ions by increasing the reactive surface area between the film and the solution under test, thereby improving pH sensitivity. In addition, we used an extended gate field effect transistor (EGFET) module to measure glucose concentrations ranging from 0 to 10 mg/ml, achieving sensitivity values of 55.4 mV/pH and 8.07 mA/mg · ml {}^{-{1}} . These findings have significant implications for the future development of blood glucose monitoring and microenvironmental sensing systems.